Design of a System to Monitor and Control Solar Pond: A Review. (March 2017) - Simic, Milan; George, Joshua
Abstract: Salinity gradient solar ponds are green energy collectors. Energy is capturedby creating a temperature gradient across the depth of the pond. All energy is from the solar radiation incident at the surface. Salinity gradient, maintained and changed with the depth, contributes to the temperature differences of up to sixty degrees. The heat generated can be used directly for a wide range of purposes, or can be converted to electricity which can be used in the plant, or shipped to the grid. Number of solar pond parameters, i.e. physical quantities, important for the correct functionality of this type of energy production plants, is mainly monitored locally, at the pond sites. Remote data acquisition (DAQ), and following that, control of the solar pond energy production, is more convenient and this is the subject of our research, reported here. With the application of wireless, or wired networks, virtual private networks and Internet a solar pond control centre could be located anywhere in the world, while the pond's sites are selected at the best solar potential places.